Does hotel size matter to get more reviews per room? - Mellinas, Juan Pedro; Martín-Fuentes, Eva (Information Technology & Tourism, 2019)
The number of reviews on websites like TripAdvisor may improve hotel ratings and hotel rankings, which favors the perception of hotel quality. Previous studies have focused on the total number of reviews for each hotel, suggesting that increasing the number of reviews could affect hotel ratings. We use a simple index, which is obtained by dividing the number of reviews on TripAdvisor for a given hotel by its number of rooms. This allows identifying the profile of the hotels that are most efficient at generating reviews on this website, which are surprisingly the smallest ones. This index also shows the real level of use of TripAdvisor in each country, without taking into account its population or number of hotels, which are elements that distort the measurement of the popularity of this website.
Keywords: reviews; hotel; TripAdvisor; rooms; Emerging; Scopus